Sustainability of Cultural Values in HR Development in Social and Intellectual Capital for Resource Excellence - Efrizon Efrizon; Masydzulhak Djamil Mz; Enny Ariyanto; Sugeng Santoso (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This literature review reveals the important role of cultural values and indigenous knowledge of local people (Indigenous people) in sustainable development and human resource development for resource advantage. Each community has developed complex practices to protect and manage its natural resources and ecosystems. The knowledge of indigenous people has been used and developed for thousands of years to carry out productive businesses and ways of organizing in the social structure of their communities. Cultural values and indigenous knowledge or local wisdom are social capital as the embodiment of traditional cultural elements that are deeply rooted, inhuman, and community life related to human resources, cultural resources, economy, security, and law.